2008
DOI: 10.1016/j.jvs.2007.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Patients with head and neck cancers and associated postirradiated carotid blowout syndrome: Endovascular therapeutic methods and outcomes

Abstract: There is no significant difference in technical and hemostatic outcomes between the reconstructive and deconstructive endovascular management methods. Hemostatic results were influenced by clinical severity. The rebleeding rate is higher in patients with advanced and acute clinical severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
136
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 14 publications
3
136
0
1
Order By: Relevance
“…Recurrence rates of 33%-86% have been quoted in prior studies. 11,17,19,20 In comparison, our rebleeding rate was (3/10) 30%. The recurrent hemorrhage rate in our series was slightly lower than that in other studies and may be due to our extended use of long-term antibiotics.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Recurrence rates of 33%-86% have been quoted in prior studies. 11,17,19,20 In comparison, our rebleeding rate was (3/10) 30%. The recurrent hemorrhage rate in our series was slightly lower than that in other studies and may be due to our extended use of long-term antibiotics.…”
Section: Discussionmentioning
confidence: 61%
“…Chang et al 16 described a delayed case of brain abscess formation as a result of septic emboli from an infected self-expandable covered stent used for CBS. Chang et al 17 also reported their experience in 24 patients with CBS who underwent endovascular therapy. Initial complications were encountered in 4 patients (36.4%) who underwent reconstructive management and in 1 patient (7.7%) who underwent deconstructive management (P ϭ .142).…”
Section: Discussionmentioning
confidence: 99%
“…8 The incidence of carotid rupture after radical neck dissection, with or without tumor resection, and multimodal therapy has been reported to be as high as 3 to 4%. 9 Although the incidence might seem low, if the 40% mortality rate is taken into account, this problem is very relevant and deserves prevention.…”
mentioning
confidence: 99%
“…Stent-grafting can preserve the affected carotid flow but has a high rate of early and delayed complications. [16][17][18][19] No significant difference in short-term outcome between stent-graft deployment and PAO has been reported, 20 and long-term results have not been reported. 17 CTA has become widely available and is sensitive and specific in the detection of hemorrhagic vascular disorders such as aneurysms, arteriovenous malformations, dural arteriovenous fistulas, and intracranial dissections.…”
mentioning
confidence: 99%